Management of water resources and health safeguards in South Asia: the present scenario - Amerasinghe, Priyanie H. (2009)
Water resources management is important for the developmental processes of any country, as the demand for water for all forms life and sectors is increasing. Closely linked to water development is health, where water acts as a vehicle for all types of diseases and plays a vital role in sanitation as well. As such, there is a great need for water resources management, to address health safeguards, which are often not looked at, in a holistic manner. Integrated Water Resources Management (IWRM) affords the best practise, for such an effort, as it aims to bring, social, economical and ecological sustainability of resources to communities. Management of water resources in relation to health requires a close collaboration of a number of stakeholders. This session looks at how different countries have looked at health opportunities through water resources management and what needs to be planned for the future in the region.